The Effects of a Self-Management Support Program via Social Media on Quality of Life of Type 2 Diabetes Patients with Comorbid Chronic Kidney Disease - Ngiewprom, Prangtip (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
This study employed a quasi-experimental, single-group pre- and post-test design to examine the effectiveness of a social media-based self-management support program on the quality of life among patients with type 2 diabetes and comorbid chronic kidney disease. A total of 45 participants completed the 12-week program, and their quality of life was evaluated using the Thai version of the WHOQOL-BREF questionnaire across four dimensions: physical, psychological, social relationships, and environment. The findings demonstrated a statistically significant improvement in overall quality of life following program participation. The mean total score increased from 65.29 ± 12.50 to 82.11 ± 15.10 (Mean difference = 16.82, t = 17.611, p < 0.001), representing a shift from a moderate to a good level of quality of life. Analysis across individual dimensions revealed statistically significant improvements in all four areas (p < 0.001). The physical dimension improved from 19.56 ± 4.09 to 24.47 ± 4.69 (t = 16.304), reflecting enhanced pain management, daily functioning, and sleep quality. The psychological dimension increased from 15.27 ± 3.77 to 19.42 ± 4.40 (t = 12.469), indicating reduced anxiety and depression alongside greater self-esteem. The social relationships dimension rose from 8.51 ± 1.96 to 11.56 ± 2.44 (t = 14.789), suggesting stronger perceived support from family and friends. The environmental dimension improved from 21.96 ± 4.33 to 26.67 ± 5.43 (t = 13.070), reflecting a heightened sense of security, improved access to healthcare services, and greater satisfaction with living conditions. These findings indicate that a social media-based self-management support program is an effective care model for patients with type 2 diabetes and chronic kidney disease, particularly in contexts where access to healthcare facilities is limited. The use of the Line OA application as a communication and health education platform demonstrates considerable potential and should be further promoted and integrated into broader healthcare delivery systems.